Biofuels from spent coffee grounds: comparison of processing routes. Issue 5 (28th May 2022) - Marx, Sanette; Venter, Roelf; Karmee, Sanjib Kumar; Louw, Jaco; Truter, Chantelle
Abstract: Bulk fuel was produced from spent coffee grounds (SCG) using different oil extraction and fuel production methods. The highest oil yield (30.2%) and energy efficiency (50%) from continuous hydrothermal liquefaction (CHTL) of the SCG, in water as a solvent, also had the lowest calorific value (37.4 MJ/kg). Oil from traditional hexane oil extraction had the highest calorific value (HHV) (38.7 MJ/kg). Renewable diesel yields through hydrotreatment of extracted oils were consistently higher than biodiesel yields through enzymatic transesterification of the same oils. The highest renewable diesel yield (15.8%) from batch HTL derived bio-oil had the highest calorific value (46.2 MJ/kg). However, the highest kerosene yield (9%) was obtained from in situ renewable diesel production through direct hydrotreatment of the SCG. The study showed that hydrothermal liquefaction was more efficient in producing oil from SCG than traditional solvent extraction but at the cost of losing valuable phytosterols present in the feedstock. As a bulk fuel, renewable diesel had a higher energy value than biodiesel, making it easier to blend into existing transportation fuels. The study provides useful information for the development of a sustainable waste-based bio-refinery in terms of attainable yields and processing options.